Diversity, astaxanthin production, and genomic analysis of Rhodotorula paludigena SP9-15 - Sukanya Phuengjayaem; Engkarat Kingkaew; Patcharaporn Hoondee; Pornchai Rojsitthisak; Boonchoo Sritularak; Worathat Thitikornpong; Somphob Thompho; Natapol Pornputtapong; Somboon Tanasupawat (My University, 2023)
Astaxanthin is a carotenoid known for its powerful antioxidant properties. This study focused on isolating yeast strains capable of producing astaxanthin from flower and fruit samples collected in Thailand. Out of 115 isolates, 11 strains were identified that produced astaxanthin. Molecular identification techniques revealed that these isolates belonged to two species: Rhodotorula paludigena (5 isolates) and Rhodosporidiobolus ruineniae (6 isolates). Whole-genome analysis of one representative strain, R. paludigena SP9-15, identified putative candidate astaxanthin synthesis-associated genes, such as CrtE, CrtYB, CrtI, CrtS, CrtR, CrtW, CrtO, and CrtZ. High-performance liquid chromatography (HPLC) and liquid chromatography-mass spectrometry (LC-MS) confirmed astaxanthin production. Further optimization of astaxanthin production was carried out by investigating the effects of various factors on the growth rate and astaxanthin production. The optimal conditions were 40 g/L glucose as a carbon source, pH 7.5, and cultivation at 25 °C with 200 rpm for 3 days. Under these conditions, R. paludigena SP9-15 synthesized biomass of 11.771 ± 0.003 g/L, resulting in astaxanthin with a content of 0.558 ± 0.018 mg/g DCW (dry cell weight), an astaxanthin yield of 6.565 ± 0.238 mg/L, and astaxanthin productivity of 2.188 ± 0.069 g/L/day. These findings provide insights into astaxanthin production using red yeast strains from Thailand and highlight the potential of R. paludigena SP9-15 for further application.
Keywords: Rhodotorula; Yeast extract; Antioxidant Activity and Oxidative Stress